2005
DOI: 10.1037/0735-7044.119.6.1687
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of catecholamine neurotransmission in the rat anterior cingulate in effort-related decision making.

Abstract: This study examined whether catecholamine-mediated signals in the anterior cingulate cortex (ACC) contribute to effort-based decision making. Rats were tested after 6-hydroxydopamine or vehicle infusions into the ACC in a T maze cost-benefit task in which the rats could choose either to climb a barrier to obtain a high reward in one arm or run into the other arm without a barrier to obtain a low reward. Results demonstrate that infusions of 6-hydroxydopamine induced a near total loss of tyrosine hydroxylase-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 22 publications
5
53
1
Order By: Relevance
“…IC 3 shows remarkable overlap with the network suggested to underlie ''stable maintenance of task mode and strategy'' found in a functional connectivity analysis (43). Based on animal studies, it has been suggested that both the OFC and pMFC code the cost and benefit of actions in terms of reward delay (OFC) and effort (pMFC) (6,44,45). Accordingly, the network reflected in IC 3 appears to be involved in evaluating task-related costs and maintaining effort.…”
Section: Resultsmentioning
confidence: 99%
“…IC 3 shows remarkable overlap with the network suggested to underlie ''stable maintenance of task mode and strategy'' found in a functional connectivity analysis (43). Based on animal studies, it has been suggested that both the OFC and pMFC code the cost and benefit of actions in terms of reward delay (OFC) and effort (pMFC) (6,44,45). Accordingly, the network reflected in IC 3 appears to be involved in evaluating task-related costs and maintaining effort.…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine function, which has long been implicated in willingness to expend effort (Salamone, 2009;Salamone et al, 2007;Treadway et al, 2012b), may also act on these regions to affect effortful decision making (Schweimer and Hauber, 2006;Schweimer et al, 2005), and thus its contribution to cognitive effort is currently under study. The overlapping-yet-distinct effects observed in the present experiments suggest that regions not required for physical effort-based decision making, such as the prefrontal cortex, may in fact be necessary for decision making with cognitive effort costs (Schmidt et al, 2012), and the NAc' prevalence in the effort literature warrants future consideration of its involvement in choice on the rCET.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, local blockade of DA receptors, in particular the D 4 subtype, impairs both acquisition and extinction of a conditioned fear response (Pezze et al, 2003;Laviolette et al, 2005;Pfeiffer and Fendt, 2006). Similarly, different forms of decision making dependent on BLA-mPFC circuits are also impaired by depletion of DA or blockade of D 1 , D 2 , or D 4 receptors in the mPFC (Schweimer et al, 2005;Floresco and Magyar, 2006;Floresco and Ghods-Sharifi, 2007). These findings indicate that dopaminergic mediation of excitatory and inhibitory transmission in the BLA 3 mPFC pathway plays an important role in mediating emotional and cognitive processes governed by temporalfrontal lobe circuitry.…”
Section: Functional Implicationsmentioning
confidence: 99%